Comparison of the umbilical artery blood gas, nucleated red blood cell, C-reactive protein, and white blood cell differential counts between neonates of diabetic and nondiabetic mothers - Bahia Namavar Jahromi; Nahid Ahmadi; Nader Cohan; Mehdi Roshan Nia Jahromi (Elsevier, 2011)
Objective: The aim of this study was to compare the neonatal umbilical artery blood gas values, C-reactive protein (CRP) levels, nucleated red blood cells (NRBCs), and white blood cells (WBCs) differential counts between offspring's of the diabetic mothers who needed insulin during pregnancy and normal mothers after cesarean delivery. Materials and Methods: A prospective study was performed involving 68 pregnant diabetic women who needed insulin during pregnancy and 410 healthy pregnant women and their neonates with gestational ages between 35 weeks and 41 weeks. Arterial blood was analyzed for pH and blood gas values and venous blood was analyzed for CRP level, NRBC, and WBC differential counts. Results: The mean NRBC count in the neonates of diabetic mothers and healthy mothers was 560±985/μL and 202±281/μL, respectively (p<0.001). The umbilical arterial blood gas showed a lower pH (7.22±0.07 vs. 7.24±0.04, p=0.004) and a higher pCO2 (49.33±10.08 vs. 47±8.67, p=0.045) in neonates of diabetic mothers compared with the controls. Values of pO2, HCO3−, base excess, WBC differential counts, and CRP levels were almost similar in the two groups. Conclusion: Lower pH, higher pCO2, and elevated NRBC counts were found in the neonates of diabetic mothers that may be suggestive of chronic intrauterine acidosis.